PENGEMBANGAN MEDIA SMART BOX BERBASIS PERMAINAN MONOPOLI DALAM KALIMAT TRANSITIF DAN KALIMAT INTRANSITIF PESERTA DIDIK KELAS 4 SEKOLAH DASAR - Elfin Purnama Sari; Frendy Aru Fantiro; Ima Wahyu Putri Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning media is a tool that can be used to assist the teaching and learning process so that the meaning of the message conveyed becomes clearer and can attract the attention of students. Based on observations and interviews with class teachers on October 23 2023, the results of an analysis of the needs of class IV students at SDN Tlekung 02 Batu were obtained, that the school still uses learning media in the form of student books, teacher books, videos, LCD, projector and YouTube (does not vary ) thus concrete learning media is needed to support learning, especially in the material of transitive sentences and intransitive sentences. This aims to make it easier for students to understand the material and be more active in learning activities.The aim of this research is to develop smart box learning media based on the monopoly game of transitive sentences and intransitive sentences using the ADDIE model which has 5 stages, namely analysis, design, development, implementation and evaluation. The data analysis techniques carried out were qualitative data analysis and quantitative data analysis with the aim of finding out how to develop smart box learning media based on the monopoly game of transitive sentences and intransitive sentences for class IV elementary school.The development of smart box learning media based on the monopoly game of transitive sentences and intransitive sentences obtained material validation results of 92% and media validation results of 94%. Both validations are categorized as very valid for implementation. Meanwhile, the student response questionnaire received a score of 92%. And the teacher response questionnaire results were 92%. From both questionnaires, the responses were in the very good category. This can be interpreted as that the development of smart box learning media based on the monopoly game of transitive sentences and intransitive sentences can attract students' attention and interest and make them more active in the learning process.